Unlocking the Power of Cinnamon: A Detailed Review of Cinnamon Therapeutic Effects in Chronic Disease Management - Kulicka, Joanna; Bychowski, Mateusz; Kwaśna, Julia; Załęska, Adrianna; Kaźmierczyk, Izabela; Lenart, Kacper; Górski, Mateusz; Homza, Michał; Zakrzewska, Natalia; Bednarek, Szymon (Quality in Sport, 2024)
Cinnamon, a widely used spice, has gained attention for its therapeutic properties, including antioxidant, anti-inflammatory, antimicrobial, and anticancer effects. This review synthesizes current evidence on cinnamon’s potential health benefits, particularly in managing metabolic, cardiovascular, dermatological, neurological, and reproductive health conditions. A systematic search of databases like PubMed, Google Scholar, and Scopus was conducted using keywords such as "cinnamon," "cinnamaldehyde," "antioxidants," and "type 2 diabetes." A total of 32 studies were selected, covering preclinical studies, clinical trials, and reviews. The review focuses on bioactive compounds in cinnamon, such as cinnamaldehyde, cinnamic acid, and polyphenols, which help reduce oxidative stress, modulate immune responses, and improve metabolic parameters. Cinnamon also shows promise in promoting skin health, enhancing wound healing, and supporting reproductive health, especially in conditions like PCOS. However, most studies are based on animal models or in vitro experiments, with limited human clinical trials. More rigorous clinical research is needed to confirm cinnamon’s efficacy, safety, and appropriate dosages for long-term use. In conclusion, while preclinical data is promising, further human studies are crucial to fully establish cinnamon’s therapeutic potential.